Síndrome de burnout y las relaciones interpersonales de los trabajadores del Centro médico - Unidad Minera Aurífera Retamas, 2022 - Alvarado Merino, Kelly (2022)
The present investigation was carried out with the objective of analyzing the influence of burnout syndrome on the interpersonal relationships of the workers of the Medical Center - Retamas Gold Mining Unit, 2022, which had 20 workers from the medical center staff as a sample. In the process of this research, we worked with methods such as inductive - deductive, analytical, synthetic and statistical. In the same way, research techniques such as the survey and interview were used, which allowed obtaining qualitative and quantitative information with the objective that the research work be carried out with the correct analysis. Likewise, we worked with instruments such as the questionnaire and interview guide, which have allowed us to properly describe the interpersonal relationships of the Medical Center - Retamas Gold Mining Unit. The results obtained determine that burnout syndrome affects the interpersonal relationships of workers, being negative for the work environment, since communication between colleagues becomes inappropriate and the care they provide to patients is not adequate. In addition, it was observed that the burnout syndrome does not allow teamwork to develop, so labor production decreases, generating little commitment on the part of the workers with their company and patients. It was possible to show how not taking care of the emotional well-being of the workers has negative consequences in the work environment and the company's production.